2016
DOI: 10.1016/j.sajb.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of selected African sorghum landraces to progressive water stress and re-watering

Abstract: Sorghum is particularly drought tolerant compared with other cereal crops and is favoured for subsistence farming in water scarce regions of the world. This study was conducted to identify South African sorghum landraces with superior drought tolerance compared with a drought tolerant breeding line (P898012). Seedlings of 14 South African sorghum landrace accessions were initially screened for drought tolerance by assessing percentage leaf water content (LWC) during progressive water deficit. Four landraces (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 39 publications
(50 reference statements)
0
21
0
1
Order By: Relevance
“…1de; Additional file 1: Figure S1; Table 1). These findings indicated that due to scarcity of soil-water, nutrients present in the soil did not mobilize well, and plant roots could not uptake it adequately, which ultimately prevented water and nutrients flow through the xylem to the surrounding cells, as observed in other plant species under watershortage conditions [19][20][21]. Thus, the deficiency of nutrients and water eventually led to the inhibition of cell growth and elongation [21], as was also manifested in this study in terms of plant height and stem diameter (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…1de; Additional file 1: Figure S1; Table 1). These findings indicated that due to scarcity of soil-water, nutrients present in the soil did not mobilize well, and plant roots could not uptake it adequately, which ultimately prevented water and nutrients flow through the xylem to the surrounding cells, as observed in other plant species under watershortage conditions [19][20][21]. Thus, the deficiency of nutrients and water eventually led to the inhibition of cell growth and elongation [21], as was also manifested in this study in terms of plant height and stem diameter (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, drought tolerant/resistant sorghum varieties are highly water use efficient (WUE) with an extensive root system for water absorption 23 and a thick waxy cuticle that retards excessive water loss 17 . Different sorghum varieties also accumulate varying amounts of osmolytes 24 26 for osmotic adjustment during periods of drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…The sorghum genome has been sequenced 28 and is part of the growing cereal genomics resource 27 , 29 , guiding crop breeding strategies. Sorghum physiological 26 , 30 , 31 , transcriptomic 32 , 33 , and proteomic 34 37 responses to osmotic/drought stress together with computational characterization of candidate genes 38 , 39 have been conducted. However, more comparative studies are required in order to fully understand how sorghum survives in hot and dry environments that are unsuitable for most crops.…”
Section: Introductionmentioning
confidence: 99%
“…Plant leaf senescence is considered as a post-flowering drought stress symptom (Burke et al, 2013). Green plants such as sorghum have two options for maintaining a high tissue water status during periods of soil moisture deficit, either by decreasing water loss due to transpiration or by increasing water uptake (Devnarain et al, 2016). Leaf senescence reduces seriously the source-sink translocation from leaves to grain (Krupa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%